Integrated hospital and community psychiatric services and use of inpatient beds. Issue 6694 (29th July 1989) - Tyrer, P.; Turner, R.; Johnson, A. L.
Abstract : The impact of introducing a divisional psychiatric service based in the community in Nottingham in 1981 on adult psychiatric admissions (patients aged 15-65) was examined with data from the Nottingham case register. During 1980-5 the number of psychiatric admissions fell significantly (4.5% a year) compared with the national figures (0.46% a year). Admissions were reduced most for the diagnoses of affective psychosis and neurotic and personality disorders. The average duration of admission fell by 3.6% a year, and use of inpatient beds fell by 37.5%. Integrating hospital and community psychiatric services by creating sectors is a viable and economically feasible way of improving psychiatric services.